L’outil numérique au service de l’intelligence collective des territoires - Vianney Gerils (Netcom)
The current socio-economic context requires local territories, to master public spending, optimize their policies and maintain quality of life and services for the population. The efficiency of use of the facilities is a major issue for territorial managers. Today, digital knowledge shared by policy makers, users (open data, data visualization) is a first principle in the process of conception and production living spaces. In this context, digital tools are an indispensable technical means of mobilizing this knowledge, stimulation of collective intelligence at the service of sustainable development of territories. This article presents the current state of our research: the design and implementation of a digital diagnostic tool and territorial visualization to support the planned decision. Our field of investigation is localized in the Department of Val de Marne (pilot site) with ambitions to collect, share, and visualize the data cartographically: a tool for fundamental research, support for operational actions.